Effects of oxidation and hot corrosion in a nickel disc alloy - Encinas-Oropesa, Adriana; Drew, G. L.; Hardy, M. C.; Leggett, A. J.; Nicholls, John R.; Simms, Nigel J. (Cranfield University, 2008)
This paper describes work to study oxidation and hot corrosion damage in nickel disc alloy RR1000. Oxidation damage has been characterised via mass change data from thermogravimetric analyses at temperatures from 700 to 800 ºC and cyclic oxidation testing at 700 and 750 ºC. Thin oxide scales rich in Cr and Ti have been found to grow in a parabolic dependence with time. Oxidation rate constants have been correlated with temperature using an Arrhenius equation. Through the use of simplifying assumptions, mass change data have been converted to oxide thickness values. These values have been compared with observed values of oxide scale and the depth of near-surface damage, which have been measured using focused ion beam (FIB) microscopy. Hot corrosion of RR1000 has been studied in the laboratory by ‘deposit' recoat experiments at 700ºC. In these tests, samples were coated with deposits of Na2SO4/NaCl salt in a gas stream of air-300 vpm SO2. Corrosion damage has been quantified by dimensional metrology of samples before and after exposure. This enabled metal losses, i.e. the depth of corrosion pits, to be determined. Distributions of metal loss data were then generated to produce median damage values and exceedance cumulative probabilities. Finally, the effect of contaminants on the hot corrosion resistance of RR1000 has also been evaluated.
Keywords: oxidation; hot corrosion; alloy RR1000